An observational study of comorbidity and healthcare utilisation among HIV-positive patients aged 50 years and over. (July 2016) - Patel, Roshani; Moore, Thomas; Cooper, Vanessa; McArdle, Conor; Perry, Nicky; Cheek, Elizabeth; Gainsborough, Nicola; Fisher, Martin
The number of HIV-positive people aged ≥50 years is rising each year. We measured the prevalence of non-infectious illnesses and their risk factors and described healthcare use in this UK population. A cross-sectional, observational study was conducted at an outpatient HIV specialist clinic in south east England. Patients age ≥50 years were invited to complete questionnaires measuring demographics, non-infectious illnesses, medication use, lifestyle and healthcare utilisation. The response rate was 67%. Of 299 participants, 84% reported ≥1 comorbid condition and 61% reported ≥2 (multimorbidity). Most commonly reported were high cholesterol, sexual dysfunction, hypertension and depression. In multivariate analyses, age, number of years HIV-positive and duration of antiretroviral therapy remained significant predictors of comorbidity when controlling for lifestyle factors (exercise, smoking and use of recreational drugs and alcohol). Use of non-HIV healthcare services was associated with increasing comorbidity, a longer duration of HIV and recreational drug use. The majority of HIV-patients aged ≥50 years reported multiple comorbidities and this was associated with polypharmacy and increased use of non-HIV services. Further research examining the quality, safety and patient experience of healthcare is needed to inform development of services to optimally meet the needs of older HIV-positive patients.